"Doubly enantiophobic" behavior during crystallization of racemic 1, 5-dihydro-2H-pyrrol-2-one thioether. Issue 23 (21st May 2018) - Lodochnikova, Olga A.; Zaripova, Aigul R.; Fayzullin, Robert R.; Samigullina, Aida I.; Vandyukova, Irina I.; Potapova, Lubov N.; Kurbangalieva, Almira R.
Abstract : One racemate forms two conglomerates and no racemic compound. Abstract : The titled compound7 demonstrates unusual "doubly enantiophobic" behavior during crystallization. Namely, the mentioned substance forms two polymorphic modifications7a and7b that appear to be racemic conglomerates in the space groups P 21 and P 65 (or P 61 ), respectively. Both7a and7b are thermodynamically stable at certain temperature ranges. Hence, γ-lactam7 is prone to spontaneous resolution of the racemate into the enantiomers in two different ways, which is an exceptional phenomenon. Phase behavior and structure of the crystalline modifications of7 were investigated by means of single crystal and powder X-ray diffraction, differential scanning calorimetry, temperature-resolved vibration spectroscopy, and hot-stage microscopy.